Down-regulation of lncRNA SNHG5 relieves sepsis-induced acute kidney injury by regulating the miR-374a-3p/TLR4/NF-κB pathway. (21st January 2021) - Wang, Min; Wei, Jilou; Shang, Futai; Zang, Kui; Zhang, Peng
Abstract: Sepsis is an acute systemic infectious disease engendered by infectious factors, which can cause the dysfunction of multiple organs, including acute kidney injury (AKI). Recently, more and more researchers are focussing on long noncoding RNA (lncRNA) that is closely associated with the development and progression of various diseases; however, the role and mechanism of lncRNA in sepsis-induced AKI are not fully understood. Here, we found a significant increase in the expression of lncRNA small nuclear RNA host gene 5 (SNHG5) in the serum of patients with sepsis than healthy controls. Similar results were obtained from mouse model of sepsis. Further investigations revealed that knockdown of SNHG5 improves the viability and reduces the rate of apoptosis and the generation of inflammatory cytokines in HK-2 and TCMK-1 cells treated with lipopolysaccharide. Mechanistically, we showed that SNHG5 can combine with microRNA-374a-3p (miR-374a-3p), which inhibits nuclear factor-κB (NF-κB) activity by targeting TLR4. In conclusion, our results demonstrate that SNHG5 may regulate sepsis-induced AKI via the miR-374a-3p/TLR4/NF-κB pathway, therefore providing a new insight into the treatment of this disease. Graphical Abstract: